Surface-Plasmon-Polaritons-Assisted Enhanced Magnetic Response at Optical Frequencies in Metamaterials - Jing Chen; Chaojun Tang; Peng Mao; Cheng Peng; Depeng Gao; Ying Yu; Qiugu Wang; Labao Zhang (IEEE Photonics Journal, 2016)
We theoretically study the coupling of magnetic plasmon polaritons (MPPs) with propagating surface plasmon polaritons (SPPs) in a system composed of an array of metal nanowires close to a metal film with a dielectric spacer. Strong coupling between MPPs and SPPs is observed, manifested by the anticrossing behavior of the resonant positions in the reflection spectra. It creates narrow-band hybridized MPPs with Rabi-type splitting as large as 250 meV. Moreover, we also found that the coupling between the MPPs and the SPPs can be tailored by the period of the metal nanowire array to affect the magnetic response of the plasmonic structure. Above the resonant wavelength of the MPPs, coupling between two kinds of resonance modes can lead to a 20-fold enhancement of the magnetic fields in the dielectric spacer, as compared with the pure magnetic resonance upon the excitation of the hybridized MPPs, whereas below it, coupling cannot lead to a magnetic field enhancement. We suggest that this feature could offer a feasible way to achieve huge magnetic field enhancement at optical frequencies and hold promising potential applications in magnetic nonlinearity and sensors.